(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Placental Growth Factor (PlGF) level is reported to be low in preeclampsia. Recent research suggested that it can be a promising tool for predicting adverse fetomaternal outcomes compared to nonspecific biomarkers. This study evaluated the predictive accuracy of maternal serum PlGF level for adverse fetomaternal outcomes in pre-eclamptic women. Materials and methods: Seventy women with preeclampsia from the Department of Obstetrics and Gynecology of Chittagong Medical College Hospital from January 2021 to December 2021. PIGF level at admission was measured by ELISA method, and value >100 and £100 pg/ml was defined as normal and low, respectively. Patients were prospectively followed till delivery to observe fetomaternal outcomes. Results: Out of 70 women, 28 (40%) developed adverse fetomaternal outcomes. The median level of PlGF was significantly lower among women with adverse fetomaternal outcomes than their counterparts [37.0 (18.9 - 61.5) pg/ml versus 122.7 (91.3-156.3) pg/ml, p <0.001)]. From the ROC curve, the best cutoff PlGF value for prediction of adverse fetomaternal outcome was 68.9 pg/ml [Area Under Receiver Operating Characteristic (AUROC) curve = 0.934, 95% Confidence Intervals (CI): 0.862-1.0] with the sensitivity, specificity, accuracy, positive predictive value and negative predictive value of 89.29%, 92.86%, 91.43%, 89.29% and 92.86%, respectively. Low PlGF level was independently associated with adverse fetomaternal outcome [Odds Ratio (OR):16.11, 95% CI: 1.94-133.18, p<0.010]. Conclusion: This study showed that the PlGF is a good predictor of adverse fetomaternal outcomes among women with preeclampsia. JCMCTA 2023 ; 34 (2) : 111-117